1990
DOI: 10.1093/ajcp/93.4.555
|View full text |Cite
|
Sign up to set email alerts
|

Hemangioblastoma and Renal Clear Cell Carcinoma Distinguished by Means of the AgNOR Method

Abstract: In view of the difficulty encountered in distinguishing between 2 degrees renal cell carcinoma (RCC) and hemangioblastoma (HBl) in the central nervous system, the AgNOR technique has been applied empirically to a series of 16 specimens of HBl, 5 primary RCC, and 6 specimens of secondary RCC in the CNS. To avoid tautology, the nature of these was confirmed by immunostaining for epithelial membrane antigen (EMA) and factor VIII-related antigen (FVII RAg). It was found that mean nuclear AgNOR counts in the stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Renal cell carcinoma shows necrosis, mitoses and cytokeratin, vimentin and EMA immunoreactivity, which are important clues in distinction (13)(14)(15). It is also suggested that the AgNOR method is a useful adjunct in achieving the differential diagnosis of hemangioblastoma and renal cell carcinoma in the nervous system (22). Anaplastic astrocytoma and meningioma also show similarity to the tumor (23).…”
Section: Results:-mentioning
confidence: 99%
“…Renal cell carcinoma shows necrosis, mitoses and cytokeratin, vimentin and EMA immunoreactivity, which are important clues in distinction (13)(14)(15). It is also suggested that the AgNOR method is a useful adjunct in achieving the differential diagnosis of hemangioblastoma and renal cell carcinoma in the nervous system (22). Anaplastic astrocytoma and meningioma also show similarity to the tumor (23).…”
Section: Results:-mentioning
confidence: 99%